The Influence of Gender Role Attitude on Marriage Attitude in Young Adulthood - Cahyaning Widhyastuti; Nida Muthi Annisa; Ade Daniatul Mugfiroh; Balqis Nurul Fazrin (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This research is a quantitative research with regression approach, that aims to determine the impact of gender role attitudes on marriage attitudes among young adults in Indonesia. It involved 113 participants (M = 20.53), and data were collected using a Google Form that included a gender role attitude scale and a marriage attitude scale. Data analysis was conducted through simple linear regression using SPSS Version 25. The results indicate that gender role attitudes significantly influence marriage attitudes. This suggests that a person's view on gender roles can affect their perception and evaluation of marriage.